2008
DOI: 10.1002/micr.20499
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic approach of the internal mammary artery (IMA): A training model in pigs

Abstract: Endoscopic internal mammary artery (IMA) approach represents a well-established procedure in coronary bypass surgery. However, such techniques require highly trained skills that need to be mastered in experimental models before taken into the clinic. To attain such skills, our aim was to develop a training model of thoracoscopic approach for harvesting of the IMA in pig. Ten pigs of either sex, weighing 20-28 kg, were used. The thoracic cavity was accessed with the animal in a lateral decubit position, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The pigs were kept at the animal facility of the Pius Branzeu Center for Laparascopic Surgery and Microsurgery of the Victor Babes University of Medicine and Pharmacy, Timisoara, Romania. All operations were performed under general anaesthesia as previously described [7].…”
Section: Animalsmentioning
confidence: 99%
“…The pigs were kept at the animal facility of the Pius Branzeu Center for Laparascopic Surgery and Microsurgery of the Victor Babes University of Medicine and Pharmacy, Timisoara, Romania. All operations were performed under general anaesthesia as previously described [7].…”
Section: Animalsmentioning
confidence: 99%
“…The recipient vessels, which are mostly used for freeflap breast reconstruction, are the ITA and ITV. 15,16 Several authors used the porcine ITA for learning purposes 17,18 or to test new surgical techniques in cardiac surgery. 19 Recently, Nistor et al proved that the pig's ITA and ITV represent an optimal model for free-flap breast reconstruction training.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that swine models are ideal for in-vivo training of MI surgical techniques 2,18,[22][23][24] . A standardized experimental model in pigs represents a useful tool for the training of surgeons to develop their skills.…”
Section: Discussionmentioning
confidence: 99%
“…A standardized experimental model in pigs represents a useful tool for the training of surgeons to develop their skills. The model developed by Jiga et al 22 seems to have a rapid learning curve, requiring minimal experience in laparoscopic surgery, serving as a practical preparation for performing more complex procedures, such as dissection of the ITA for MI cardiac surgery. However, this model has the disadvantage that the dissection of the ITA occurs only in the proximal third, a relatively small portion (mean of 3.2 cm in length), and is devoid of branches in swine.…”
Section: Discussionmentioning
confidence: 99%